2021
DOI: 10.3390/jmse9111201
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Swirls on Slurry Flows in Horizontal Pipelines

Abstract: In deep ocean transportation pipeline, the swirling internal flow has a significant impact on the marine minerals transportation efficiency and safety. Therefore, the present work investigates various swirl flow motions for the slurry transport characteristics of the multi-sized particulate flow in a horizontal pipeline. Since the internal flow is a liquid-solid-solid mixture, a steady-state three-dimensional Eulerian-Eulerian multiphase approach in conjunction with the k-ω SST turbulence model is implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…106 The application of swirling flow intensified the turbulence motion, thus improving the dispersion of solid particles and minimizing the wear on the pipe walls and the pipe blockage. 107 Such turbulence motion enhanced the mixing of fluids and, hence, improved the mass transfer performance. 108−110 To induce such swirling flow in microreactors might provide another option to keep a good dispersion of solid (catalyst) particles in the liquid flow and enhance the liquid−solid mass transfer.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…106 The application of swirling flow intensified the turbulence motion, thus improving the dispersion of solid particles and minimizing the wear on the pipe walls and the pipe blockage. 107 Such turbulence motion enhanced the mixing of fluids and, hence, improved the mass transfer performance. 108−110 To induce such swirling flow in microreactors might provide another option to keep a good dispersion of solid (catalyst) particles in the liquid flow and enhance the liquid−solid mass transfer.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…The improved transportation of particle-laden liquids has been shown in large-sized conduits through the creation of swirling flow patterns, e.g., using pipes with continuously varying cross sections or attaching helical blades inside pipes . The application of swirling flow intensified the turbulence motion, thus improving the dispersion of solid particles and minimizing the wear on the pipe walls and the pipe blockage . Such turbulence motion enhanced the mixing of fluids and, hence, improved the mass transfer performance. To induce such swirling flow in microreactors might provide another option to keep a good dispersion of solid (catalyst) particles in the liquid flow and enhance the liquid–solid mass transfer.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…In this study, settling behaviours of slurries in partially filled pipelines was investigated and a correlation for predicting the settling rate of particles was developed based on the experimental data. Shi et al [47] investigated the impact of swirls on slurry flow in horizontal pipelines. The author concluded that increasing the intensity swirls flow from pipe inlet is beneficial to multi-sized slurry transportation because it hinders particles deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of fine particles is found to reduce energy consumption by changing the coarse particle's flow regime. Shi et al [38] carried out simulations on multi-sized slurry flows in the horizontal pipeline under various swirling motions utilizing the Eulerian-Eulerian multiphase model in conjunction with the k-ω SST scheme. The results suggest that an increased level of swirl results in a higher degree of homogeneity of slurry flows.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, most of the reported research is mainly concerned with the slurry transport for the lab-scale data for Newtonian liquids [34][35][36][37][38]42], while several industrial slurry systems likely exhibit complex non-Newtonian behaviors [43][44][45]. On the other hand, secondary phases like droplets and bubbles play a significant role in industrial scales pipeline transport such as oil sand tailings and mining residuals [46][47][48].…”
Section: Introductionmentioning
confidence: 99%